Global impact of parasitic infections and the importance of parasite control - Kaminsky, Ronald; Mäser, Pascal (Frontiers in Parasitology, 2025)
Parasites have a severe impact on animal and human health. Parasites like worms, ticks, mites, fleas, biting flies, mosquitoes, and pathogenic protozoa affect humans and their pets as well as their livestock globally, both in terms of severity and numbers. Parasitic infections are a global phenomenon, and they can be associated with severe or mild symptoms but represent a continuous risk of severe diseases for animals and humans. Therefore, effective treatment options and the prevention of infection are key for the wellbeing of pets, livestock, and humans, including the reduction of zoonotic risk of infection. The effective control of parasites in animals can greatly improve their quality of life and is also beneficial for humans; this is threatened by drug-resistant parasite populations. Today’s key areas for improvement of parasite control are as follows: a) convenience of prevention and treatment, b) effectiveness against drug-resistant parasites, c) availability and reduced costs of treatment, and d) control measurements that are environmentally friendly.